The impact of social and family role stress on the achievement motivation of Indian teachers - Zulfiqar-Ullah Siddiqui; Mahvish Fatima; Hafiz Mohd. Ilyas Khan (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
For many students and teachers achievement motivation has become not just an essential part of vocational life but also infringing even on the quality of social, family and work life. Achievement motivation has been studied as one of the most positive aspect of students’ life while, occupational or role stress has been linked with individuals’ social, family and organizational sector. This study examines the impact of social and family stress on the achievement motivation of school and college teachers in Aligarh, India. Statistical analyses of questionnaire returns of 200 teachers reveal that the impact of social and family role stress was not significant on the achievement motivation of the subjects. This insignificant relationship may be attributed to the fact that Indian school as well as college teachers keep their social and family stress separate from their achievement motivation. This separation was made possible because the teachers were academically and professionally successful and this enabled them to distinguish between their personal and professional domains of life and not allowing any undue interference of outside events or happenings.